Bacterial cellulose: a versatile biopolymer for wound dressing applications - Portela, Raquel (2019)
Although several therapeutic approaches are available for wound and burn treatment and much progress has been made in this area, room for improvement still exists, driven by the urgent need of better strategies to accelerate wound healing and recovery, mostly for cases of severe burned patients. Bacterial cellulose (BC) is a biopolymer produced by bacteria with several advantages over vegetal cellulose, such as purity, high porosity, permeability to liquid and gases, elevated water uptake capacity and mechanical robustness. Besides its biocompatibility, BC can be modified in order to acquire antibacterial response and possible local drug delivery features. Due to its intrinsic versatility, BC is the perfect example of a biotechnological response to a clinical problem. In this review, we assess the BC main features and emphasis is given to a specific biomedical application: wound dressings. The production process and the physical-chemical properties that entitle this material to be used as wound dressing namely for burn healing are highlighted. An overview of the most common BC composites and their enhanced properties, in particular physical and biological, is provided, including the different production processes. A particular focus is given to the biochemistry and genetic manipulation of BC. A summary of the current marketed BC-based wound dressing products is presented, and finally, future perspectives for the usage of BC as wound dressing are foreseen.